1990
DOI: 10.1136/oem.47.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Liquid/air partition coefficients of four terpenes.

Abstract: The liquid/air partition coefficients of four common terpenes, a-pinene, ,B-pinene, 3-carene, and limonene, have been determined in vitro using head space technique. The liquids used were water, human blood, and olive oil. a-Pinene, P-pinene, and 3-carene were practically insoluble in water The aim of the present study was to determine the in vitro blood/air, oil/air, and water/air partition coefficients of four common terpenes: a-pinene, ,Bpinene, 3-carene, and limonene. Materials and methods CHEMICALSThe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 11 publications
(2 reference statements)
3
46
0
Order By: Relevance
“…The average relative uptake of a-pinene, of the two higher concentrations, was 59 % (table 1), lower than that for styrene (68 %) but higher than that for toluene (49 %) in similar experiments (14,15). The partition coefficients between the blood and air for toluene and a-pinene are of the same magnitude, while the corresponding coefficient for styrene is higher (4,16). Metabolic rate and fat solubility may be other reasons for the differences in the relative uptake between the three solvents.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The average relative uptake of a-pinene, of the two higher concentrations, was 59 % (table 1), lower than that for styrene (68 %) but higher than that for toluene (49 %) in similar experiments (14,15). The partition coefficients between the blood and air for toluene and a-pinene are of the same magnitude, while the corresponding coefficient for styrene is higher (4,16). Metabolic rate and fat solubility may be other reasons for the differences in the relative uptake between the three solvents.…”
Section: Discussionmentioning
confidence: 55%
“…The high solubility of terpenes in blood and adipose tissue should imply a high respiratory uptake and accumulation in adipose tissues (4). The respiratory and percutaneous uptake of terpenes has been observed in man (5,6), but no quantitative study was found regarding absorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) was also applied to data on the partitioning of four terpenes (Falk et al, 1990) and four gases (Steward et al, 1973) in human blood. Both chemical classes are not included in the data of Table 1.…”
Section: Human Tissue Partition Coefficientsmentioning
confidence: 99%
“…e proportions of MTs vary with season, species and locality. According to the documented physicochemical properties of MTs, 2) they are sparingly soluble in water but are soluble in blood and lipophilic tissues. α-and β-Pinene dominate emissions from conifer trees and research investigations have raised concerns regarding the physiological e ect of α-pinene on humans.…”
Section: Introductionmentioning
confidence: 99%